Proteomic Analysis of Differentially Expressed Proteins in Fenneropenaeus chinensis Hemocytes upon White Spot Syndrome Virus Infection - Li, Wei (Public Library of Science, 2014)
To elucidate molecular responses of shrimp hemocytes to white spot syndrome virus (WSSV) infection, two-dimensional gel electrophoresis was applied to investigate differentially expressed proteins in hemocytes of Chinese shrimp (Fenneropenaeus chinensis) at 24 h post infection (hpi). Approximately 580 protein spots were detected in hemocytes of healthy and WSSV-infected shrimps. Quantitative intensity analysis revealed 26 protein spots were significantly up-regulated, and 19 spots were significantly down-regulated. By mass spectrometry, small ubiquitin-like modifier (SUMO) 1, cytosolic MnSOD, triosephosphate isomerase, tubulin alpha-1 chain, microtubule-actin cross-linking factor 1, nuclear receptor E75 protein, vacuolar ATP synthase subunit B L form, inositol 1,4,5-trisphosphate receptor, arginine kinase, etc., amounting to 33 differentially modulated proteins were identified successfully. According to Gene Ontology annotation, the identified proteins were classified into nine categories, consisting of immune related proteins, stimulus response proteins, proteins involved in glucose metabolic process, cytoskeleton proteins, DNA or protein binding proteins, proteins involved in steroid hormone mediated signal pathway, ATP synthases, proteins involved in transmembrane transport and ungrouped proteins. Meanwhile, the expression profiles of three up-regulated proteins (SUMO, heat shock protein 70, and arginine kinase) and one down-regulated protein (prophenoloxidase) were further analyzed by real-time RT-PCR at the transcription level after WSSV infection. The results showed that SUMO and heat shock protein 70 were significantly up-regulated at each sampling time point, while arginine kinase was significantly up-regulated at 12 and 24 hpi. In contrast, prophenoloxidase was significantly down-regulated at each sampling time point. The results of this work provided preliminary data on proteins in shrimp hemocytes involved in WSSV infection.